KORELASI GAYA PENGAJARAN GURU, GAYA PEMBELAJARAN MURID PRINSIP PERAKAUNAN DAN MINAT DALAM KEUSAHAWANAN (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract Aspirations Education Development Plan 2013-2025 in sub element of equity targeting students for academic excellence as a goal to be expected. To achieve these aspirations, the role of teachers and pupils are given special attention. In addition, the rate of dependence on employment is expected to be reduced by injecting the interest of students to become entrepreneurs after school. The Ministry of Education has initiated this effort by integrating elements of entrepreneurship in each subject. Accordingly, this study aimed to identify the relationship between teachers and teaching styles and learning styles of pupils in order to raise the academic achievement of pupils and students participating graduates. The study found that all elements of their teaching in teaching style model Grasha (1996) and learning styles in fact a students learning style inventory Selmes (1987) are discussed. Furthermore, the Career Development Model Holland (1974) analyzed to identify interests participating graduates after school will also be discussed. Some implications and recommendations were given them, teachers need to identify students learning style before applying the teaching force. Compatibility between teaching and learning styles will impact on the academic achievement and career interests of students.Keywords: Grasha teaching styles, Selmes learning styles, Holland development career, interest in entrepreneurship